Implications of Transmigration Program Implementation Towards Transmigrant Welfare Levels - Febriansyah Febriansyah; Irwan Natakesuma (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to determine the factors contributing to the transmigration program to the welfare level of transmigrants and compare aspects of the development of the welfare level of transmigrants at transmigration locations from before and after people become transmigrants. The research was conducted at the Transmigration location, Fajar Baru Village, Panca Jaya District, Mesuji Regency. The method used is quantitative, using questionnaires and document searches that are relevant to the research topic. The results showed that transmigrants were still categorized as poor or underprivileged. Some of the things that cause this situation include: First, the transmigrants do not have permanent jobs and only rely on work as farmers; and Second, the rice fields they own still have not produced anything, because the harvest period has not yet entered so that many transmigrants change professions to become casual workers. Practical implications can be done by carrying out more effective coaching by paying attention to the economic, socio-cultural, and mental-spiritual fields.